Implementasi Full Day School sebagai Strategi Branding Sekolah di MTs Zainul Falah - Islam, Izul; Khadavi, M Jadid (Al-Jadwa: Jurnal Studi Islam, 2024)
Curriculum transformation and evolving global needs increasingly influence changes in Indonesia's educational landscape, including Islamic educational institutions. MTs Zainul Falah has adopted the full-day school model as a strategy to improve educational quality and strengthen school branding within the competitive Islamic education environment. This study aims to analyze the implementation of the full-day school program at MTs Zainul Falah and its impact on the school's image and reputation. This study employs a qualitative research method, utilizing data collection techniques such as observation, documentation, and interviews, to provide a comprehensive understanding of the experiences and perspectives of the various stakeholders involved. The results show that the implementation of the full-day school program at MTs Zainul Falah is effective in improving educational quality and the school’s image in the eyes of the community. The program not only positively impacts students' academic development but also strengthens the school's reputation within the surrounding community. Overall, the full-day school program at MTs Zainul Falah has proven to be an effective branding strategy, solidifying the school’s position as a competent and trusted Islamic educational institution. This study highlights full-day school as an effective branding strategy to enhance community appeal and trust in Islamic educational institutions.